Renoprotective Effect of Total Glucosides of Paeony (TGP) and Its Mechanism in Experimental Diabetes - Yonggui Wu; Kejun Ren; Chao Liang; Liang Yuan; Xiangming Qi; Jing Dong; Jijia Shen; Shanyan Lin (Elsevier, 2009)
Total glucosides of paeony (TGP), extracted from the root of Paeonia lactiflora pall, has been shown to have ant-inflammatory and antioxidative actions. The aims of this study were to elucidate the renoprotective effect of TGP and its mechanism in experimental diabetes. Streptozotocin-induced diabetic rats were treated with TGP for 8 weeks. Treatment with TGP at 50, 100, and 200 mg/kg significantly lowered 24-h urinary albumin excretion rate in diabetic rats. TGP treatment in all doses markedly attenuated glomerular volume, and treatment with TGP at 100 and 200 mg/kg markedly reduced indices for tubulointerstitial injury in diabetic rats. Western blot analysis showed that the expressions of 1α (IV) collagen, intercellular adhesion molecule (ICAM)-1, interleukin (IL)-1, tumor necrosis factor (TNF)-α, NF-κB p65, and 3-nitrotyrosine (3-NT) protein were increased in the kidneys of diabetic rats; the increases in these proteins were all dose-dependently and significantly inhibited by TGP treatment. The expression of nephrin protein was significantly reduced in the kidneys from diabetic rats and markedly increased by TGP treatment. The expression of transforming growth factor (TGF)-β1 protein in the kidney was also significantly increased in diabetic rats, which was significantly inhibited by treatment with TGP at all doses. Our data suggest that TGP treatment ameliorates early renal injury via the inhibition of expression of ICAM-1, IL-1, TNF-α, and 3-NT in the kidneys of diabetic rats. Keywords:: diabetic nephropathy, total glucosides of paeony (TGP), intercellular adhesion molecule (ICAM)-1, interleukin (IL)-1, tumor necrosis factor (TNF)-α